Предельные лимитанты в задачах динамики для прямоугольной призмы - Папков, С.О.; Чехов, В.Н. (Прикладная механика, 2013)
Розглянуто алгоритм розв'язку квазірегулярної нескінченної системи лінійних алгебричних рівнянь, яка відповідає крайовій задачі усталених вимушених коливань ізотропної прямокутної призми в постановці плоскої задачі лінійної теорії пружності. Алгоритм базується на використанні лімітант Кояловича, що дозволяє обчислювати верхні й нижні оцінки для всієї нескінченної послідовності невідомих, а також власні частоти призми. Додатково в області прямокутника знайдено суми всіх функціональних рядів у представленні розв'язку крайової задачі. An algorithm is considered of solving the quasi-regular infinite system of linear algebraic equations, which corresponds to the boundary value problem of stationary forced vibrations of isotropic rectangular prism in the statement of plane deformed state of linear theory of elasticity. The algorithm is based on using the Koyalovich’s limitants, what permits to evaluate the upper and lower estimates for all the infinite sequence of unknowns as well as the natural frequencies of prism. Additionally, the sums of all the functional series from the solution representation are found in the area of rectangular.